Low-dose exposure of intestinal epithelial cells to formaldehyde results in MAP kinase activation and molecular alteration of the focal adhesion protein paxillin - Feick, Peter; Haas, Stephan; Singer, Manfred V.; Böcker, Ulrich (Toxicology, 2006)
We investigated the potential pathophysiological role of non-lethal formaldehyde concentrations on human intestinal epithelial HT-29 cells. Expression levels of actin, tubulin and detectable cytokeratin isoforms 5, 13, 18, 19 and 20 were not affected after 24h of exposure to 1mM formaldehyde. By contrast, cellular organization of cytoskeletal constituents was already changed after 60min. Within 15min, formaldehyde induced profound tyrosine phosphorylation of the focal adhesion protein paxillin and of proteins at about 120-130kDa. Concomitantly, phosphorylation of ERK-1/2 and p38 MAP kinase occurred. Paxillin was not only tyrosine phosphorylated but underwent a sustained molecular weight shift representing serine/threonine phosphorylation that was independent of MAP kinase activity and EGF-R-mediated signalling. Our data show that exposure of intestinal epithelial cells to low-dose formaldehyde is followed by rapid and profound signalling events. The data suggest a modifier role of environmental or endogenous formaldehyde for epithelial cell functions.